Multiomic analysis of Schistosoma mansoni reveals unique expression profiles in cercarial heads and tails - James R. Hagerty (Nature Portfolio, 2021)
James R. Hagerty et al. generate transcriptomic and proteomic profiles of heads and tails from larval schistosome worms. Their results identify unique expression and translational profiles between these macrostructures, providing further insight into the cell biology of a prominent human pathogen.